PENGARUH E-SERVICE QUALITY DAN PERCEIVED RISK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BUKALAPAK (Studi pada Konsumen Bukalapak di Kota Semarang) - Tsaqifa Zaina Taqianie; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2019)
The purpose of this research was to know the influence of e-service quality variable and vperceived risk variable on the buying decision. the population was all Bukalapak consumers who stayed in Semarang, and the sample was 100 Bukalapak consumers who were taken by purposive sampling technique. The type of this research was explanatory research. This research used quantitative analysis with validity test, reliability test, coefficient correlation, coefficient determination, simple regression analysis, multiple regression analysis, t-test, F-test, helped by microsoft excel and SPSS 21.0.  The result of this research showed that e-service quality and perceived risk variable had a very strong, significant and positive influence on the buying decision. it meant, the better e-service quality and perceived risk, the higher buying decision of Bukalapak consumers. the suggestion of this research was maximizing the service on the Bukalapak’s website and giving the guarantee to the personal data consumer, and also the more guaranteed-payment guarantee, so consumers had a better perception to the Bukalapak.